(untitled) (Third Sector Social Economic Review, 2024)
This study aims to analyze Turkey’s and Brazil’s presence in Africa in terms of political economy within the framework of the foreign policy principles adopted after the Cold War. In this context, the basic foreign policy principles of both countries are emphasized theoretically and practically. In this study, the deductive method and qualitative data collection methods are used. In the first part, where Turkey’s foreign policy and political economy are examined, it is seen that in parallel with the tool of development aid in foreign policy, development aid-intensive approach is also displayed in Africa, and the active presence of the business world in the region has a determining power in Turkey’s economic policies. Collaborative pursuits in Brazil’s foreign policy are similarly reflected in relations with Africa, and the discourse of ""development cooperation"" is emphasized. For Brazil, African continent is an important resource for strengthening their presences in global system. Although Turkey’s starting point in Africa is not purely economic, it provides economic contribution in terms of results. Brazil also prioritizes development and South-South cooperation as well as obtaining economic benefits in terms of its results. Africa is an region that strengthens the capacities of both countries in the global competitive system.